Catheter ablation of left atrial arrhythmias on uninterrupted oral anticoagulation with vitamin K antagonists: What is the relationship between international normalized ratio, activated clotting time, and procedure‐related complications?. (1st September 2017) - Kottmaier, Marc; Bourier, Felix; Semmler, Verena; Telishevska, Martha; Koch‐Büttner, Katharina; Lennerz, Carsten; Lengauer, Sarah; Kornmayer, Marielouise; Rousseva, Elena; Brooks, Stephanie; Brkic, Amir; Grebmer, Christian; et al.
Abstract: Background: Ablation of atrial fibrillation (AF) on uninterrupted phenprocoumon reduces periprocedural thromboembolic and bleeding complications. Heparin is administered intraprocedurally to achieve activated clotting times (ACT) of 300–400 seconds. We investigated the effect of international normalized ratio (INR) on ACT and intraprocedural heparin requirements. Moreover, safety of a target ACT of 250–300 seconds was investigated. Methods and results: We studied 949 patients referred for AF or left atrial tachycardia ablation. Patients were divided into Group 1 (n = 249) with an INR <2 and Group 2 (n = 700) with an INR ≥2. Mean INR was 1.7 ± 0.13 in Group 1 and 2.3 ± 0.25 in Group 2. Baseline, mean, minimum and maximum ACT were significantly lower in Group 1 (138 ± 17 seconds vs. 145 ± 21 seconds; 281 ± 28 seconds vs. 288 ± 29 seconds; 251 ± 36 seconds vs. 258 ± 34 seconds; 307 ± 32 seconds vs. 316 ± 40 seconds; P <0.05). Intraprocedural heparin requirements adjusted to body weight were lower in Group 1 (127 ± 41 U/kg vs. 122 ± 40 U/kg). Weak correlations between INR and baseline, mean, minimum and maximum ACT as well as intraprocedural heparin requirements were observed. No differences regarding major or minor complications were found. INR and periprocedural anticoagulation parameters had no influence on major complications. No thromboembolic complications were observed in both groups with a target ACT value of 250–300 seconds. Conclusions: There is only a weak correlation between INR, intraprocedural ACT, and intraprocedural heparin requirements. Periprocedural target ACT of 250–300 seconds seems safe and does not increase periprocedural bleeding and thromboembolic complications in patients undergoing RF ablation on uninterrupted phenprocoumon therapy.